2013
DOI: 10.3109/0167482x.2012.760540
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s willingness to opt for external cephalic version

Abstract: We conclude that expected pain during treatment and the success rate are the most important factors influencing the willingness to undergo ECV. Taking this information into account when counseling for ECV and reassuring women that unbearable pain is always a reason to stop ECV, and that the vast majority of women reported that the experienced pain is bearable, might improve the uptake of ECV and decrease the number of CS due to breech presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…Other studies have described women’s experiences of having a breech presenting baby [2224] and ECV [13, 14, 2527]. Our findings add to the understanding of women’s experiences with a breech-presenting baby in the late third trimester of pregnancy as many women are offered an ECV,…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Other studies have described women’s experiences of having a breech presenting baby [2224] and ECV [13, 14, 2527]. Our findings add to the understanding of women’s experiences with a breech-presenting baby in the late third trimester of pregnancy as many women are offered an ECV,…”
Section: Discussionsupporting
confidence: 62%
“…This study describes Australian women’s experiences who underwent an ECV which resulted in a baby who remained a breech presentation. Other studies have described women’s experiences of having a breech presenting baby [ 22 24 ] and ECV [ 13 , 14 , 25 27 ]. Our findings add to the understanding of women’s experiences with a breech-presenting baby in the late third trimester of pregnancy as many women are offered an ECV,…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, between 1995 and 2001, the number of patients aware of the procedure had significantly increased (52.7% to 73.2%) but the number of those willing to consider it had decreased from 52.7% to 23.9% 3 . Others have suggested that concerns about pain may be an important factor in women declining the offer of ECV, making up to 30% of patients favour C-Section instead 4,5 .…”
mentioning
confidence: 99%
“…Several authors have already demonstrated that analgesic use increases the ECV success rate, thus showing that success may be directly associated with the pain the procedure can induce. Moreover, another study has showed that the two factors affecting motivation to undergo ECV are pain, with intense pain‐reducing motivation (OR 0.11, 95% CI 0.05‐0.23), and success rate, which increases willingness when high (OR 3.42, 95% CI 2.04‐5.74) . After we drafted our initial protocol, a prospective study was published comparing N 2 O/O 2 use in ECV for 150 women (September 2009‐December 2010) with ECV with no analgesia for 150 others (January‐August 2009) .…”
Section: Discussionmentioning
confidence: 99%